2022
DOI: 10.1002/ptr.7520
|View full text |Cite
|
Sign up to set email alerts
|

Isobavachalcone: A comprehensive review of its plant sources, pharmacokinetics, toxicity, pharmacological activities and related molecular mechanisms

Abstract: Isobavachalcone (IBC), also known as isobapsoralcone, is a natural flavonoid widely derived from many medicinal plants, including Fabaceae, Moraceae, and so forth. IBC has been paid more and more attention by researchers in recent years due to its pharmacological activity in many diseases. This review aims to describe in detail the plant sources, pharmacokinetics, toxicity, pharmacological activities, and molecular mechanisms of IBC on various diseases. We found that IBC can be obtained not only by extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 151 publications
(152 reference statements)
0
14
0
Order By: Relevance
“…Because TSP50-induced cell proliferation and tumorigenesis are dependent on the activation of the NF- k B signaling pathway [ 78 ], it has been suggested that the antiproliferative effect of cardamonin could be related to the inhibition of TSP50/NF-κB protein expression [ 79 ]. Furthermore, the ability to suppress cancer proliferation via the inhibition of NF-κB signaling has also been reported in several other chalcones, such as 4-Boc-piperidone chalcones [ 80 ], bichalcone analogs [ 81 ], IBC [ 82 ], hydroxysafflor yellow A [ 83 ] and butein [ 84 ].…”
Section: Molecular and Cellular Mechanisms Of Actionmentioning
confidence: 98%
“…Because TSP50-induced cell proliferation and tumorigenesis are dependent on the activation of the NF- k B signaling pathway [ 78 ], it has been suggested that the antiproliferative effect of cardamonin could be related to the inhibition of TSP50/NF-κB protein expression [ 79 ]. Furthermore, the ability to suppress cancer proliferation via the inhibition of NF-κB signaling has also been reported in several other chalcones, such as 4-Boc-piperidone chalcones [ 80 ], bichalcone analogs [ 81 ], IBC [ 82 ], hydroxysafflor yellow A [ 83 ] and butein [ 84 ].…”
Section: Molecular and Cellular Mechanisms Of Actionmentioning
confidence: 98%
“…Flavonoids are well-known to possess a variety of biological activities with therapeutic interests such as antioxidant [ 5 ], antimalarial [ 6 ], anti-inflammatory [ 7 , 8 ], antiviral [ 9 , 10 ], antibacterial [ 11 ], antidiabetic [ 8 ], antifungal [ 12 ], and anticancer [ 1 , 13 , 14 , 15 , 16 ] potential. It is also reported that they protect the cardiovascular system from oxidative stress as a consequence of their ROS scavenger ability [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These natural bioactive compounds belong to different chemical classes such as phenolic acids, terpenoids, flavonoids, alkaloids, and terpenoids [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Moreover, flavonoids are considered as the most abundant and diverse family [ 17 , 18 ] with promising therapeutic benefits since they are non-toxic molecules with many biological activities including anticancer [ 19 ], inflammatory [ 20 ], antibacterial [ 21 ], antiviral [ 22 ], neuroprotective effects [ 23 ], and other activities. On the other hand, if their proprieties are properly used, these natural products could be efficient, safe, and new therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%